Reconnecting Creativity: Designing Learning Kits through Hands-On Material Exploration for Early Childhood Development - Amelia, Amanda; Paskevicius, Algirdas; Ono, Kenta (Aliansi Desainer Produk Industri Indonesia (ADPII), 2025)
Designing creative learning kits for children during early childhood development requires a deep understanding of how they interact with simple, open-ended materials. This study explored the idea that designers must reconnect with hands-on material experiences to create meaningful and effective kits. Using the